My eyes got a bit watery there: using stories to explore emotions in coaching research and practice for injured, sick and wounded military personnel. Issue 2 (3rd July 2017) - Douglas, Kitrina; Carless, David
Abstract: Recognising the importance of holistic approaches to sport coaching pedagogy, there has been a move to include and understand more fully emotional and subjective features of coaches' work. Our research here seeks to advocate for and support this pedagogy. Ethnographic data were collected at a golf intervention where civilian sport coaches worked among serving injured, sick and wounded military personnel in a recovery context. We adopted a storytelling methodology to render present aspects of sport coaching that have previously been absent, particularly those of emotional and empathic understanding. This form of analysis and representation allowed multiple, dialogic meanings to evolve and a more sophisticated understanding of the role and contribution of the coach/leader in this unusual disability sport context. Through a series of vignettes which represented different aspects of the intervention, light is shed on how emotions are evoked, hidden or made visible depending on different situations and relationships. The stories also show some of the potential costs or risks of becoming more empathic and caring. Feedback from the coaches and programme participants suggested the stories illuminated some aspects of their lives, work and relationships that remain difficult to articulate and share.